OpenShift OKD on IBM LinuxONE, installation guides - Zaki, Narjisse; Carta, Sylvain; Dini, Alexandre; Ferguson, Neale (IBM redpaper., 2019)
This document provides the step-by-step instructions for installing OpenShift OKD 3.10 on LinuxONE. The intended audience is Systems Architects and Specialists who design, size, and implement solutions on IBM® infrastructures.